(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2020)
Due to the rapid spread of the novel coronavirus SARS-CoV-2 (COVID-19), medical protective equipment is in high demand. In order to cover the need for these protective materials, frames for face shields, for instance, can be produced flexibly, quickly and decentrally in small quantities through 3D printing. In this study, Fused Deposition Modeling (FDM) is used for the production of corresponding components from Polylactide plus (PLA+) and Polyethylene terephthalate glycol (PETG) material. Stereolithography (SLA) is also used to produce high-quality frames from a photopolymer. The frames are presented and examined with regard to their manufacturing technology features and surface properties.